Development of ultra-pure gadolinium sulfate for the Super-Kamiokande gadolinium project. (12th December 2022) - Hosokawa, K; Ikeda, M; Okada, T; Sekiya, H; Fernández, P; Labarga, L; Bandac, I; Perez, J; Ito, S; Harada, M; Koshio, Y; Thiesse, M D; et al.
Abstract: This paper reports the development and detailed properties of about 13 metric tons of gadolinium sulfate octahydrate, $\rm Gd_2(\rm SO_4)_3· \rm 8H_2O$, which has been dissolved into Super-Kamiokande (SK) in the summer of 2020. We evaluate the impact of radioactive impurities in $\rm Gd_2(\rm SO_4)_3· \rm 8H_2O$ on diffuse supernova neutrino background searches and solar neutrino observation and confirm the need to reduce radioactive and fluorescent impurities by about three orders of magnitude from commercially available high-purity $\rm Gd_2(\rm SO_4)_3· \rm 8H_2O$ . In order to produce ultra-high-purity $\rm Gd_2(\rm SO_4)_3· \rm 8H_2O$, we have developed a method to remove impurities from gadolinium oxide, Gd2 O3, consisting of acid dissolution, solvent extraction, and pH control processes, followed by a high-purity sulfation process. All of the produced ultra-high-purity $\rm Gd_2(\rm SO_4)_3· \rm 8H_2O$ is assayed by inductively coupled plasma mass spectrometry and high-purity germanium detectors to evaluate its quality. Because of the long measurement time of high-purity germanium detectors, we have employed several underground laboratories for making parallel measurements including the Laboratorio Subterráneo de Canfranc in Spain, Boulby in the UK, and Kamioka in Japan. In the first half of production, the measured batch purities were found to be consistent with the specifications. However, in the latter half, the $\rm Gd_2(\rm SO_4)_3· \rm 8H_2O$ contained one order of magnitude more 228 Ra than the budgeted mean contamination. This was correlated with the corresponding characteristics of the raw material Gd2 O3, in which an intrinsically large contamination was present. Based on their modest impact on SK physics, they were nevertheless introduced into the detector. To reduce 228 Ra for the next stage of gadolinium loading to SK, a new process has been successfully established.